Legal Aspects of E-Commerce in India: Challenges and Opportunities - Dr Madhura Shukla (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
The tremendous growth of online shopping in India has revolutionised the sector and opened up new possibilities for vendors and buyers. The complicated legal issues brought about by this expansion, however, need for a regulatory structure that is both strong and flexible. This article delves into the legal elements of online shopping in India, specifically addressing important concerns including data security, cybersecurity, consumer rights, taxes, and IP. It looks at how well current legislation like the Consumer Protection (E-Commerce) Rules, 2020 and the Information Technology Act, 2000 handle these problems. The study brings attention to the inadequacies in the present legal framework and suggests ways policies might be improved to create an environment where e-commerce can thrive while being safe and efficient. This article examines case studies and current legislative developments in India to highlight the need of legal reform in e-commerce. It argues that change is crucial for achieving sustainable growth and gaining customer confidence. With the aim of informing lawmakers, lawyers, and e-commerce industry players, this research seeks to strengthen and broaden participation in the digital economy.